Analysis of the Effect Quality Service on Telkomsel Customer Satisfaction in Karawang with the Servqual Method (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
This study aims to determine the effect of service quality an important factor of the service business is the assessment of service quality which is strongly influenced by the perceptions and expectations of each customer. The dimensions of service quality are divided into 5 main dimensions, namely: reliability, responsiveness, assurance, empathy and tangible.This study includes associative research or relationships using quantitative approach. The sample in this study was Telkomsel customers in Karawang Regency who used the MyTelkomsel application. A sample of 100 respondents was determined the sampling snowball method. The research instrument was in the form of a questionnaire. The results of the analysis using SPSS version 16 show that: (1) Reliability influences customer satisfaction (2) Responsiveness influences customer satisfaction (3) Assurance and certainty influences consumer satisfaction (4) Empathy influences customer satisfaction (5) Tangible influences to customer satisfaction.